An antioxidant self-healing hydrogel for 3D cell cultures. Issue 7 (24th January 2020) - Yang, Lei; Zeng, Yuan; Wu, Haibo; Zhou, Chunwu; Tao, Lei
Abstract : An antioxidant self-healing hydrogel has been facilely prepared using the Biginelli reaction and then used for 3D cell culture. Abstract : In this paper, an antioxidant self-healing hydrogel has been prepared. The Biginelli reaction was used to prepare a monomer containing phenylboronic acid (PBA) and 3, 4-dihydropyrimidin-2(1 H )-one (DHPM) groups. This PBA–DHPM monomer was copolymerized with poly(ethylene glycol methyl ether) methacrylate (PEGMA) to produce a water-soluble copolymer via radical polymerization. The resulting copolymer quickly crosslinked poly(vinyl alcohol) (PVA) through borate ester bonds to generate a self-healing hydrogel under mild conditions (pH ∼ 7.4, 25 °C). The prepared hydrogel showed an inherent antioxidant ability because of the DHPM moieties in the hydrogel structure. It also showed no cytotoxicity, and in an in vivo mouse model the hydrogel injected under the skin of a mouse hardly caused any adverse reactions, suggesting that this hydrogel could be used as an implantable biomaterial. This first report of an antioxidant self-healing hydrogel demonstrates a new application of the Biginelli reaction in materials science, which might prompt a broad study of multicomponent reactions in interdisciplinary fields.